A personalized medication management platform (PMMP) to improve medication adherence: A randomized control trial. (March 2017) - Huang, Chu-Ya; Nguyen, Phung-Anh Alex; Clinciu, Daniel L.; Hsu, Chun-Kung; Lu, Jui-Chia Richard; Yang, Hsuan‐Chia; Wu, Chieh-Chen; Tsai, Wen-Chen; Chou, Yueh-Ching; Kuo, Terry B.J.; Chang, Po-Lun; Jian, Wen-Shan; et al.
Highlights: Addressed medication non-adherence, an important aspect in healthcare which significantly influences patients' health and expenses to patients, healthcare providers and insurance companies. The PMMP platform implemented and tested through a randomized control trial to improve medication adherence, self-management of medication, and reducing long-term medication costs. The PMMP platform significantly reduced medication delays and missed medications and can therefore enhance patient health and overall disease and healthcare management. Abstract: Objectives: Medication non-adherence caused by forgetting and delays has serious health implications and causes substantial expenses to patients, healthcare providers, and insurance companies. We assessed the effectiveness of a personalized medication management platform (PMMP) for improving medication adherence, self-management medication, and reducing long-term medication costs. Methods: We developed a mobile PMMP to reduce delayed and missed medications. A randomized control trial was conducted of three medical centers in Taiwan. A total 1198 participants who aged over 20 years, received outpatient prescription drugs for a maximum period of 14 days. 763 patients were randomly assigned to intervention group as receiving daily SMS reminders for their medications and 434 patients in control group did not. The primary outcome was change in delaying and forgetting medication between before and after intervention (after 7 days). Results: Medication delays were reduced from 85% to 18% (67% improvement) after SMSs for the intervention group and from 80% to 43% (37% improvement) for the control group. Patients forgot medications were significantly reduced from 46% to 5% (41% improvement) for the experimental group after SMSs and from 44% to 17% (27% improvement) for the control group. The SMSs were considered helpful by 83% of patients and 74% of them thought SMSs help in controlling diseases. 92% of patients would recommend this system to their family and friends. Conclusions: A timely and personalized medication reminder through SMS can improve medication adherence in a nationalized healthcare system with overall savings in medication costs and significant improvements in health and disease management. Trial registration: ClinicalTrials.gov: NCT02197689.